Comparative study between delto-pectoral and deltoid splitting approach in surgical treatment of proximal humerus fractures using philos plating - Singh, Harpreet; Agarwal, Kamal K.; Patel, Meet; Makadia, Prashant; Jain, Pranjal; Oza, Bineet (International Journal of Research in Orthopaedics, 2022)
Background: The present study was done to compare the two approaches of proximal humerus PHILOS plating on the basis of functional outcome of patients and other perioperative parameters. Methods: 40 patients with type 2 and type 3 proximal humerus were assigned to group A and B pre-operatively using random alternate allocation. Patients in group-A were operated with deltoid splitting approach while patients in group-B were operated with delto-pectoral approach. Functional outcome was assessed at 6 weeks, 3-months and 6-months. Perioperative parameters like duration of surgery, associated complications, and hospital stay were also noted and compared. Results: In each group, there were 12 two-part fractures and 8 three-part fractures. For 2-part fractures the mean duration of surgery was 51.33 min for group A and 63.37 min for group B. While for 3-part fractures it was 67.5 min and 80 min respectively. Irrespective of fracture type, there was statistically significant difference between the constant scores in both groups at 3 months (2-part: group A: 67.67; group B: 44.7; p value=0.001. 3-part: group A: 66; group B: 48; p value=0.001). However, the difference between two groups at 6 months was not statistically significant. Conclusions: Both approaches show satisfactory outcomes over a long period. However, the significantly less operative time and minimal soft tissue dissection in deltoid splitting approach can be used as an advantage in particular cases. Moreover, there was an early return to day-to-day activities for the deltoid splitting group which should be considered when treating an active individual.